Digital Transformation in Media & Society - Akkor Gul, Aysen; Dilek Erturk, Yildiz; Elmer, Paul (Istanbul University Press, 2020)
This book presents examples of digital transformation as they have unfolded in different fields and in different countries. Thus it is designed to be a situation analysis in which some chapters share research results and others are essays written to contribute to the ongoing debate. The book consists of two parts, the first being "Transformation in Television, Radio, Film and Games" and the second being "Transformation in Social Life, Economy and Education". Individual chapters' authors address different issues related to the digitalization of games, post-production, radio transmission, education, marketing, payment systems, fandom, social media, artificial intelligence, democracy, and intellectual creativity. Three questions to be kept in mind as you read each chapter are "What is happening in the particular field as a result of digital transformation?", "Is it a real transformation?", and "What are the benefits and drawbacks of the transformation?" Chapter One focuses on new trends in television-viewing practices and considers how digitalization empowers TV series' fans. The chapter draws attention to the popularity of Turkish television series in Latin America and argues that digitalization has transformed the habits and attitudes of Latin American viewers: through the spread of Turkish television series, Turkish culture and values are also promoted. Chapter Two consists of a case study that sheds light on whether technological developments will transform the image of women in online games. In-depth interviews with female users of massively multiplayer online role-playing games and a game producer reveal that although technology gives women players a chance to be whatever they want, they prefer to create gendered characters. Thus women's participation in digital technology has not transformed the representation of gender in online games just yet. Chapter Three focuses on "vertical editing" techniques as an outcome of the digital transformation of post-production methods. Exploring the limitations of these techniques through a documentary film called Kamilet, the chapter raises the ethical issues inherent in vertical editing owing to its ability to manipulate information through image formation. Chapter Four analyses the transformation of the body in fiction and shows how the development of science and technology affects our understanding of metamorphosis in movies ranging from fantastic classics to science-fiction. The chapter concludes that human beings embrace their individuality firmly and will not abandon their self-image for that of a robot, an android, a digital avatar, or even a clone of oneself. Chapter Five examines podcasts as an outcome of transformation of digital data processing. Presenting a sample of Turkish radio broadcasts, it argues that podcasting is just a complementary application rather than a new form of radio. Chapter Six compares the recent digitalization of "public education" in two European countries-Hungary and Turkey. It reveals both the achievements and the shortcomings of ICT and compares and contrasts digital educational competencies in these countries. One of the striking findings of this chapter is that in both countries, digital content and the digital literacy levels of teachers are unsatisfactorily below expectations. Chapter Seven sheds light on the virtual "socialization practices" of digital culture in closed groups. It defines the characteristics of "field", "doxa" and "social capital" in digital habitus as constructed on Facebook and tries to understand the digital transformation of habitus based on Bourdieu's theory. Chapter Eight draws attention to digital transformation in marketing techniques such as "kid influencer marketing". It introduces "toy unboxing videos" on YouTube as one of the new ways in which brands reach consumers. It asserts that although toy unboxing videos allow more interaction when compared to traditional methods, they are no less innocent. Chapter Nine takes a brief look at social media and how artificial intelligence, social media, and fake news represent a danger to democracy while revealing also how AI can be used to safeguard democracy. The chapter concludes with food for thought as to what a future might look like where AI potentially dominates politics. Chapter Ten presents an example of the digital transformation of payment systems and describes existing mobile money systems, with particular attention being given to their untapped potential in Turkey. It concludes with a socioeconomic image of what effective mobile money systems in Turkey would look like and offers key directions for future development and deployment of mobile money in Turkey in pursuit of the country's national agenda of becoming cashless by 2023.